Citizen participation and democratic practices: An analysis from the use of social networks and schooling (Revista de Investigaciones Universidad del Quindío, 2022)
There are numerous studies (Norris, 2001; Muñiz, 2015; Díaz and Góngora, 2019) that have declared the importance of the use of social networks and the education of citizens as essential areas to understand civic and democratic participation in issues of sociopolitical interest. . The present work is carried out with the objective of analyzing the association between the variables schooling and use of social networks (YouTube, Facebook and Twitter) to be informed of matters of national interest. For which, a subsample of 20,323 subjects selected from the National Survey of Civic Culture of the year 2020 was used. The selection criterion was to be 18 years old and over. The research hypothesis was that schooling and the use of social networks (Facebook, Twitter and YouTube) are associated in promoting citizen participation in issues of national interest and issues of democratic life. The results showed that, in effect, as the specialized literature points out, there is an association relationship between the variables of interest and citizen participation in issues of sociopolitical interest. To carry out the statistical analysis, the chi2 test was used to determine the association between the study variables, finding a value = 2050.1, with a significance p = 0.05. Therefore, the research hypothesis is verified.
Keywords: media; civic culture; democratic participation; elections; citizens